Screen time and adolescents' mental health before and after the COVID-19 lockdown in Switzerland: A natural experiment - Marciano, Laura; Viswanath, Kasisomayajula; Morese, Rosalba; Camerini, Anne-Linda (Frontiers in Psychiatry, 2022)
Background: During the Covid-19 lockdown in 2020, adolescents’ mental health was largely undermined. A general increment in screen time was reported. However, the long-term effects of the latter on adolescents’ mental health are still little explored. Methods: In the present natural experiment, we investigated these effects using longitudinal data collected before and after the first lockdown in Switzerland. Data come from 674 Swiss adolescents (56.7% females, Mage=14.45, SDage=.50) during Spring 2019 (T1) and Autumn 2020 (T2) as part of the longitudinal MEDIATICINO study. Self-reported mental health measures included somatic symptoms, inattention, anxiety, irritability, anger, sleep problems, obsessive-compulsive symptoms, loneliness, and depression. Measures for screen-media activities included time spent on the Internet, smartphone, social media, video gaming, instant messaging, and television viewing. They were all assessed at T1 and T2. Results: Paired-sample t-tests with Bonferroni’s correction showed that most mental health problems increased over time with an overall medium effect size (g=.337). Also, medium effect sizes were shown for anxiety, depression, and inattention; small-to-medium effect sizes for loneliness, sleep problems, and obsessive-compulsive symptoms; and a small effect size was found for somatic symptoms. Screen-media activities increased, except for television viewing and video gaming. The results of the hierarchical regression analyses showed that, controlling for covariates, increased time spent on social media – calculated as the difference between T2 and T1 – was the only screen-media activity significantly associated with worse mental health at T2 (β=.112, p=.016). More time spent in structured media activities like television viewing diminished levels of inattention (β=-.091, p=.021) and anxiety (β=-.093, p=.014). Among covariates, being female, experiencing two or more life events, having mental health problems at T1, and using screens for homeschooling negatively influenced mental health at T2. Conclusion: These results align with literature indicating a small but negative effect of social media on mental health. Underlying mechanisms are manifold, including increased exposure to Covid-19 news, heightened fear of missing out, social comparison, and time-displaced for activities such as physical activity and green time. However, in line with the structured days hypothesis, getting involved in media-structured activities like television viewing might protect against mental health symptoms.